Efforts to Promote Reintegration and Rehabilitation of Traumatized Former Child Soldiers: Reintegration of Former Child Soldiers in Sierra Leone: The Role of Caregivers and Their Awareness of the Violence Adolescents Experienced During the War - Borisova, Ivelina I. (J Aggress Maltreat Trauma, 2013)
This article explores the role of caregivers in the reintegration of former child soldiers from Sierra Leone. Using data on 282 youth and their respective caregivers, our aim is to focus on the caregiver–child relationship after reintegration. We investigate the extent to which caregivers know about child soldiers' experiences of direct and indirect violence, as well as involvement in war activities. We further examine variables that might shape the degree of caregiver knowledge of child's war experiences. Finally, we examine if caregiver knowledge of war experiences is associated with child's psychosocial outcomes. Findings highlight the importance of developing thoughtful programs that consider the needs of the child in the context of the family and caregivers with whom he or she is reunified.